AGE AND GROWTH OF RIBBONFISH TRICHIURUS LEPTURUS LINNAEUS - Narasimham, K A (Indian Journal of Fisheries, 2011)
The ribbonfishes form an important group of food fish along the Andhra coast and among them Trichiurus lepturus Linnaeus is the dominant species. Except for the work of Prabhu (1955) and some comments by Tampi et al (1971), there is no other published information from Indian waters on age and growth of the species. This aspect has been dealt with in this article.